2015
DOI: 10.1177/1759091415569908
|View full text |Cite
|
Sign up to set email alerts
|

AAV-Mediated Gene Delivery in a Feline Model of Sandhoff Disease Corrects Lysosomal Storage in the Central Nervous System

Abstract: Sandhoff disease (SD) is an autosomal recessive neurodegenerative disease caused by a mutation in the gene for the β-subunit of β-N-acetylhexosaminidase (Hex), resulting in the inability to catabolize ganglioside GM2 within the lysosomes. SD presents with an accumulation of GM2 and its asialo derivative GA2, primarily in the central nervous system. Myelin-enriched glycolipids, cerebrosides and sulfatides, are also decreased in SD corresponding with dysmyelination. At present, no treatment exists for SD. Previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 46 publications
0
54
0
Order By: Relevance
“…Previous reports showed that all treated cats had clearly preserved neurologic function and improved disease phenotype, though mild symptoms such as fine tremors and slight hind limb weakness were present. Also, previously published postmortem analysis revealed above-normal levels of Hex activity throughout the brain and spinal cord, with clearance of GM2 ganglioside storage (McCurdy et al, 2015, Rockwell et al, 2015). Microglia from treated cats retained a ramified morphology and lacked expression of MHC-II in regions of cleared storage such as the thalamus (Fig.…”
Section: Resultsmentioning
confidence: 54%
See 4 more Smart Citations
“…Previous reports showed that all treated cats had clearly preserved neurologic function and improved disease phenotype, though mild symptoms such as fine tremors and slight hind limb weakness were present. Also, previously published postmortem analysis revealed above-normal levels of Hex activity throughout the brain and spinal cord, with clearance of GM2 ganglioside storage (McCurdy et al, 2015, Rockwell et al, 2015). Microglia from treated cats retained a ramified morphology and lacked expression of MHC-II in regions of cleared storage such as the thalamus (Fig.…”
Section: Resultsmentioning
confidence: 54%
“…Seven SD cats were treated with monocistronic AAVrh8 vectors encoding feline HEX α and β subunits between 4-7 weeks of age, prior to symptom onset. Two treatment cohorts were based on injection route: bilateral thalamic and DCN injection (n=3) (McCurdy et al, 2015) or bilateral thalamic and unilateral ICV injection (n=4) (Rockwell et al, 2015) (Table 1). Treated SD cats were euthanized 16 weeks after injection, an age comparable to the humane endpoint of untreated SD cats.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations